Strengthening Character Education of Students Through Civics Caring Apps Based on M-Learning During the Covid-19 Pandemic - Mutiara Imtisyal Ammatulloh; Noviani Permana; Rizwan Firmansyah; Lussy Nur Sa’adah; Zahra Ihsani Izzatunnisa; Dwi Iman Muthaqin (Indonesian Journal of Educational Research and Technology, 2022)
The purpose of this study was to increase the effectiveness and efficiency of character education for students using M-Learning-based media containing content and display according to the needs and interests of students at the elementary school level. The method used is the Design and Development research method, with data collection carried out including literature studies, interviews, validation with experts, and questionnaires. The final results of this study are user tasks, evidence of student character changes, prototype designs, and mobile applications in providing an understanding of character values with a good user experience and displaying content that is in accordance with the needs and interests of students so that they are motivated to implement every positive character value they learn. This is because Civics Caring Apps provides customized types of text, graphics, audio, video, quizzes, animations, and interactivity to allow everyone to access various forms of media to create more meaningful programs for users. Based on the research that has been done, the online learning process (on the network) has hampered the process of internalizing character education in students. The presence of Civics Caring Apps has been proven to increase the effectiveness and efficiency of the character-building process of students during the Covid-19 pandemic.